Growth of coffee seedlings under different soil cultivation systems and family farming drip irrigation - Ferrarezi, Rhuanito Soranz; Deus, Fábio Ponciano de; Martins, Guilherme Alonso; Primo, Renan; Testezlaf, Roberto (Coffee Science - ISSN 1984-3909, 2015)
Family farming is critical for Brazilian food security and economy. However, this sector has low investment capacity, which results in low utilization of production technologies. Alternative soil cultivation systems and inexpensive drip irrigation needs to be tested for family farming. The aim of this study was to evaluate different soil cultivation systems and the use of KIFNET™ drip irrigation in the initial vegetative growth of coffee (Coffea arabica L.) ‘Catuaí’ in an Oxisol. We tested three soil cultivation systems (plowing and harrowing/CONV; subsoiling at 30 cm/SS; and scarification, fertilization at 60 cm and harrowing/TO) and two irrigation treatments (irrigated and non-irrigated). The irrigation management addressed the crop water requirements by monitoring weather conditions using an automatic weather station and calculating the ETo using the Penman-Monteith equation. There were significant differences among the soil cultivation systems and irrigation (p<0.01). Treatments with CONV soil cultivation system presented higher plant height, stem diameter, number of branches and canopy width compared to the other soil cultivation systems (13.8%, 10%, 16%, and 19.2% respectively) (p <0 01). Irrigated treatments were 12.8%, 39.7%, 34.8%, and 25.8% higher than non-irrigated ones for the same variables (p <0.01). SS and TO soil cultivation systems presented no effect at the initial development stage because of the shallow root system. The tested drip irrigation system can be a low-cost alternative for irrigation in family farming.